The effectiveness and characteristics of physiotherapy interventions on adults with iliotibial band syndrome. A scoping review - Christofi, Iakovos; Ploutarchou, George; Savva, Christos; Karagiannis, Christos (Journal of bodywork and movement therapies, 2024)
Although physiotherapy remains one of the main interventions suggested for the treatment of Iliotibial Band Syndrome (ITBS), the appropriate physiotherapy and its effectiveness on this injury haven't been fully defined yet. This study aims to investigate which are the appropriate physiotherapy interventions and their effectiveness in adults with ITBS PRISMA extension for Scoping Reviews and Template for Intervention Description and Replication checklist were used. Medline, Cinahl, SPORTDiscuss, and Pascal Archive databases were searched to identify trials involving patients with ITBS and healthy adults who underwent any form of physiotherapy with or without medication, compared with those who underwent any form of physiotherapy with or without medication or no treatment. The methodological quality of studies was assessed with the PEDro scale. Seven studies, with a total sample of 187 subjects, met the inclusion criteria. Physiotherapy interventions like physical modalities, manual therapies, exercises, and multimodal interventions are effective with or without medication in the improvement of patients' pain, functionality, muscle strength, and iliotibial band stiffness. However, a treatment plan with multimodal interventions and medication may increase the patients' iliotibial band stiffness, and deep transverse frictions aren't recommended for the management of patients' pain and functionality. The overall reporting quality of interventions was poor. The small number of studies and their methodological quality don't allow for firm conclusions. There is moderate-evidence to suggest that physiotherapy with or without medication is effective in adults with ITBS. Well-designed randomized controlled trials are required to elucidate the efficacy and proper parameters of physiotherapy in these patients.